2017
DOI: 10.17219/acem/63999
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the changes in enzymatic antioxidant reserves and lipid peroxidation in chosen parts of the brain in an animal model of Parkinson disease

Abstract: Background. Parkinson's disease is a progressive neurodegenerative disorder, characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta. The causes of Parkinson's disease are not fully understood; however, increasing evidence implicates oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Anyway, studies in the animal models of PD showed different outcomes compared to the human sample analysis with a degree of controversy [182, 183] probably due to the temporal length of the experimental observation time.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Anyway, studies in the animal models of PD showed different outcomes compared to the human sample analysis with a degree of controversy [182, 183] probably due to the temporal length of the experimental observation time.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Nonmotor symptoms in PD, however, constitute lack of attention, executive dysfunction, working memory issues, and visuo-spatial impairment . Notably, the hippocampus plays an important role in executive function and memory performance suggesting that the hippocampus has a role in PD …”
Section: Introductionmentioning
confidence: 99%
“…3 Notably, the hippocampus plays an important role in executive function and memory performance suggesting that the hippocampus has a role in PD. 20 Our objective is to make a comparative analysis of GSH levels in tandem with susceptibility (metal ions, e.g., iron, etc.) in the SN and hippocampus regions of the PD and agematched control subjects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, several studies on post-mortem PD patients’ brains pointed out the accumulation of 4-HNE-protein adducts in the nigrostriatal neurons and LBs [ 16 , 75 ]. Similarly, rat models of PD injected with 6-OHDA displayed significantly increased MDA concentration and acrolein-bound proteins, specifically in the striatum [ 76 , 77 ]. Also, the 4-HNE and MDA content in plasma and cerebrospinal fluid of PD patients was found to be significantly higher compared to healthy subjects, thus hinting at their quantification as potential biomarkers for PD [ 16 , 78 - 80 ].…”
Section: Introductionmentioning
confidence: 99%